RUbioSeq+: A multiplatform application that executes parallelized pipelines to analyse next-generation sequencing data. (January 2017) - Rubio-Camarillo, Miriam; López-Fernández, Hugo; Gómez-López, Gonzalo; Carro, Ángel; Fernández, José María; Torre, Coral Fustero; Fdez-Riverola, Florentino; Glez-Peña, Daniel
Highlights: RUbioSeq+, a multiplatform application for the integrated analysis of NGS data, is presented. It implements pipelines for analysing SNVs, CNVs, bisulfite-seq and ChIP-seq experiments, using well-established tools. It also includes a new GUI designed for research groups where bioinformaticians and biomedical researchers work together. To our knowledge, there is no other current application with similar characteristics and utilities for NGS data analysis. RUbioSeq+ results have been already validated and published. Abstract: Background and objective: To facilitate routine analysis and to improve the reproducibility of the results, next-generation sequencing (NGS) analysis requires intuitive, efficient and integrated data processing pipelines. Methods: We have selected well-established software to construct a suite of automated and parallelized workflows to analyse NGS data for DNA-seq (single-nucleotide variants (SNVs) and indels), CNA-seq, bisulfite-seq and ChIP-seq experiments. Results: Here, we present RUbioSeq+, an updated and extended version of RUbioSeq, a multiplatform application that incorporates a suite of automated and parallelized workflows to analyse NGS data. This new version includes: (i) an interactive graphical user interface (GUI) that facilitates its use by both biomedical researchers and bioinformaticians, (ii) a new pipeline for ChIP-seq experiments, (iii) pair-wise comparisons (case–control analyses) for DNA-seq experiments, (iv) and improvements in the parallelized and multithreaded execution options. Results generated by our software have been experimentally validated and accepted for publication. Conclusions: RUbioSeq+ is free and open to all users athttp://rubioseq.bioinfo.cnio.es/ .